INFLUENCE OF MIXTURE VARIABLES ON THE FLEXIBILITY OF HOT ROLLED SHEET - AHMAD ZAMHARI, KEMAS
The objective of the investigation described in this paper was to study the influence of certain material and environmental variables on the flexibility of hot rolled sheet mix. The flexibility of the mix is expressed in terms of its tensile strength value. The measurement of tensile strength was conducted by using the indirect tensile or split test. It was found that increasing of stone content up to 40 per cent, or filler content up to 3 per cent above the specification, tends to increase the flexibility. While increasing of loading temperature tend to reduce the flexibility. Linear correlation between Marshall stability and indirect tensile strength give a better relationship than that for indirect tensilestrength and Marshall Quotient. Thiscorrelation and other studies on fatigue resistance of gap-graded mixes permit determination of maximum Marshall stability for a good fatigue resistance.